Deskripsi Analisis Yuridis Kekerasan Seksual dalam Perspektif Hukum Pidana di Indonesia - Faturohman Faturohman; Irwanto Irwanto; Rt. Septia Ningsih (Program Studi Hukum Keluarga Islam (Ahwal Syakhshiyyah), Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2024)
This research examines the juridical analysis of sexual violence from the legal perspective that applies in Indonesia. The crime of sexual violence in criminal law, in the criminal justice mechanism for dealing with sexual harassment behavior. Sexual harassment is the mildest but most frequent form of sexual violence. Many victims do not receive a sense of justice because so far there has been no strict regulation regarding sexual harassment in Indonesian criminal law. By using normative juridical research methods, and equipped with an in-depth approach to criminal law policy. The results obtained from writing this article are that the regulation of criminal law regarding sexual harassment is included as a crime of decency in general. In enforcing criminal law against sexual harassment in the criminal justice system process in Indonesia, the police, prosecutors and judges are involved, so its implementation still faces technical, juridical problems, especially the problem of evidence, in addition, the underlying thinking of law enforcement officials is still dogmatic normative juridical. Sexual harassment is carried out using Articles 281 to 294 of the Criminal Code, where the definition of acts that violate decency and obscene acts is returned to the feelings of decency of the local community and places the element of the victim's dislike as the most important element for the law to be enforced in Indonesia. Penelitian ini mengkaji mengenai analisis yuridis kekerasan seksual dalam perspektif hukum yang berlaku di Indonesia. Tindak pidana kekerasan seksual dalam hukum pidana, dalam mekanisme peradilan pidana untuk menangani perilaku pelecehan seksual. Pelecehan seksual merupakan bentuk kekerasan seksual yang paling ringan tetapi paling sering terjadi. Banyak korban yang tidak mendapatkan rasa keadilan karena sejauh ini belum ada pengaturan yang tegas tentang pelecehan seksual dalam hukum pidana Indonesia. Dengan menggunakan metoda penelitian yang bersifat yuridis normatif, serta dilengkapi dengan pendalaman pendekatan kebijakan hukum pidana. Diperoleh hasil dari penulisan artikel ini, bahwa pengaturan hukum pidana mengenai pelecehan seksual dimasukkan sebagai tindak pidana kesusilaan secara umum. Dalam penegakan hukum pidana terhadap pelecehan seksual dalam proses sistem peradilan pidana di Indonesia melibatkan kepolisian, kejaksaan dan hakim, sehingga pelaksanaannya masih menghadapi problema teknis secara yuridis terutama masalah pembuktian, di samping itu yang melandasi pemikiran para aparat penegak hukum masih yuridis normatif dogmatik. Pelecehan seksual dilakukan dengan menggunakan Pasal 281 hingga 294 KUHP yang mana definisi perbuatan melanggar kesusilaan dan perbuatan cabul dikembalikan kepada perasaan kesusilaan masyarakat setempat dan menempatkan unsur ketidaksukaan korban sebagai unsur terpenting untuk dapat ditegakkannya hukum di Indonesia.